(-)-Epicatechin Mitigates High Fat Diet-induced Inflammation in the Hippocampus and Altered Recognition Memory in Mice. (29th May 2020) - Kang, Jiye; Wang, Ziwei; Oteiza, Patricia
Abstract: Objectives: This project investigated the capacity of dietary (-)-epicatechin (EC) to mitigate hippocampal inflammation and impaired memory in high fat diet (HFD)-fed mice. Methods: Healthy 6 weeks old male C57BL/6J mice (10 mice/group) were fed for 13 weeks either: a control diet (10% total calories from fat), a high fat diet (60% total calories from lard fat), or the control and high fat diets supplemented with 20 mg EC/kg body weight. Between weeks 10 and 12 of the dietary intervention, object recognition memory was evaluated by the novel object recognition task and short-term spatial memory by the object location memory task, and the Morris Water Maze. After 13 weeks on the dietary treatments, mice were euthanized, and brain tissues and blood were collected. Hippocampus was isolated, flash-frozen in liquid nitrogen, and stored at −80°C. Metabolic endotoxemia was assessed by measuring plasma lipopolysaccharide (LPS) levels. Gene expressions related to inflammation (Toll-like receptor 4 (TLR4) and tumor necrosis factor-α (TNF-α)), activation of microglia (ionized calcium-binding adapter molecule 1 (Iba-1)), and oxidative stress (NADPH oxidase 4 (NOX4)) were analyzed in the hippocampus with RT-qPCR. Results: After 13 weeks on the dietary treatments, HFD-fed mice developed obesity, endotoxemia, and showed increased parameters of hippocampal inflammation, i.e., high mRNA levels of TLR4, Iba-1, and NOX4. While not affecting body weight gain, EC supplementation prevented all other HFD-induced changes. Impaired recognition memory was observed in HFD-fed mice, which was prevented by EC supplementation. Neither HFD consumption nor EC supplementation affected mouse spatial memory. Conclusions: EC supplementation prevented short-term recognition memory in HFD-induced obese mice, which could be in part due to the capacity of EC to mitigate metabolic endotoxemia and associated hippocampal inflammation and oxidative stress. Funding Sources: HA Jastro Shields Award.